Psychological Distress and Associated Issues among Cancer Patients - Mbowe, Godfrey Livingstone; Ambakisye, Simion; Lubawa, Dorothy (Medical Research and Its Applications Vol. 1, 2024)
Introduction: The psychological distress to cancer patients is defined as a multifactorial unpleasant emotional experience psychologically such as cognitive, behavioral, emotional, and social, as well as spiritual. It interferes with the ability to cope effectively with cancer, its physical symptoms and its treatment. Aim: The present study aimed to identify the psychological distress among cancer patients at KCMC, and to explore the relationship between demographic characteristics of cancer patients and psychological distress. Methodology: The study was conducted at KCMC, a zonal hospital in Moshi Municipality, Kilimanjaro Region situated in the northeast of Tanzania at the lower slope of Mount Kilimanjaro. The study used a sample of 175 respondents. The study was cross-sectional design, a quantitative approach. The data gathered for the study were analyzed using quantitative data analyzing software SPSS version 20 and were visually presented using descriptive statistics such as frequency distribution of tables, and figures. Results: The findings of the study showed that the majority of the respondents (cancer patients) 105 (60.0%) were experiencing psychological distress among the cancer patients. Cancer patients who are divorced and widowed experience anxiety (p-value 0.01) significantly. Those who were low in education were significantly affected with (p-value 0.03) anxiety and (p-value 0.01) depression. The variable in economic; the less satisfaction was significant (p-value 0.01) were experiencing adjustment disorder. The study experienced anxiety and depression more than the younger cancer patients, which means below 40 years. Therefore, according to the findings of this study revealed that younger were less affected compared with middle-aged people. Conclusion and Recommendation: In order to address the psychological discomfort that cancer patients endure, the study suggests that it is critical to include psychologists on the treatment team. Additionally, since a study indicated that 60% of cancer patients experience psychological discomfort, the oncology department should become interested in conducting research on psychological distress management.